1996
DOI: 10.1021/om9507585
|View full text |Cite
|
Sign up to set email alerts
|

P−C Bond Cleavage of Phosphorus-Bridged [1]Ferrocenophane Coordinated to the [Cp(CO)2Fe]+ Fragment

Abstract: An iron complex with (1,1‘-ferrocenediyl)phenylphosphine (FCPP) as a ligand, [Cp(CO)2Fe(FCPP)]+, was prepared, and its PF6 - salt was subjected to X-ray crystal structure analysis. Photoirradiation of the PF6 - salt resulted in Cp ring migration from a P to an Fe atom. Addition of H2O or (n-Bu)4NF to the reaction mixture gave an isolable complex, formulated as [Cp(CO)Fe(C5H4FeC5H4PFPh)]. The structure for one of the racemic isomers was determined with X-ray analysis. This isomer was a kinetic product and isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…However, the boron adducts do successfully undergo thermal ROP. Miyoshi and co-workers [217,218] reported a complementary route to both the thermal and TM-catalyzed methods to afford phophorus-bridged polymers by ROP upon UV irradiation and successfully polymerized metal-bearing ferrocenophanes fcPPh[MLn] to afford the highly metalized polymers 62a-c with M w 2.2 × 10 4 and M n 2.2 × 10 4 for 62b as given in Fig. 43.…”
Section: Phosphorus-containing Polymersmentioning
confidence: 99%
“…However, the boron adducts do successfully undergo thermal ROP. Miyoshi and co-workers [217,218] reported a complementary route to both the thermal and TM-catalyzed methods to afford phophorus-bridged polymers by ROP upon UV irradiation and successfully polymerized metal-bearing ferrocenophanes fcPPh[MLn] to afford the highly metalized polymers 62a-c with M w 2.2 × 10 4 and M n 2.2 × 10 4 for 62b as given in Fig. 43.…”
Section: Phosphorus-containing Polymersmentioning
confidence: 99%
“…[105,112] Strained phospha [1]ferrocenophanes 29 can also coordinate through the lone pair on phosphorus to metal fragments (Scheme 4), [113][114][115][116][117] which alternatively may insert into a PÀC bond (Scheme 5). [118,119] Stable phosphonium-bridged [1]ferrocenophanes, sulfurized P V derivatives, and borane adducts of (phenyl)phospha[1]-ferrocenophanes (31) have been prepared and in some cases and subjected successfully to thermal transition-metal-catalyzed ROP. [120,121] Notably, the enthalpies of thermal ROP recorded for (phenyl)phospha [1]ferrocenophane (29, R = Ph, À68 AE 5 kJ mol À1 ) [120] and (methylphenyl)phosphonium [1]ferrocenophane (31, R 1 = Ph, R 2 = Me, À61 AE 5 kJ mol À1 ) suggest slightly smaller strain energies than the typical values for dialkylsila [1]ferrocenophanes despite larger average tilt angles, though this is probably a consequence of the presence of the bulky phenyl substituent.…”
Section: Ansa Complexesmentioning
confidence: 99%
“…The two PMe 3 ligands on the platinum center were observed at -27.9 and -25.9 ppm, which are assigned to the PMe 3 groups cis and trans with respect to the bridging phosphido group, respectively. The structure was confirmed by X-ray analysis, as shown in Figure 2, where the W(CO) 5 and Pt(PMe 3 ) 2 fragments are connected through the ferrocenylphenylphosphido bridge in a manner similar to that found in 4. From the two reactions described above, it is found that phosphido-bridged heterodinuclear complexes can be obtained through the insertion reaction of the Pt-(PMe 3 ) 2 fragment into the P-C bond of the fcpp-metal complex (eq 5).…”
Section: Resultsmentioning
confidence: 60%
“…The reaction of 1,1′-ferrocenediylphenylphosphine (1), abbreviated as fcpp, with CpMn(CO) 2 (THF) or W(CO) 5 -(THF) gave CpMn(CO) 2 (fcpp) (2) or W(CO) 5 (fcpp) (3), respectively. 9 2 thus obtained was allowed to react with Pt(PMe 3 ) 4 in toluene at 70°C for 6 h. With silica gel column chromatography, the product was isolated in low yield, probably due to partial decomposition during the chromatography in the air, because the 31 P{ 1 H} NMR spectrum of the reaction mixture showed that an isolated species was a major product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation